HE4 and CA-125 kinetics to predict outcome in patients with recurrent epithelial ovarian carcinoma: the META4 clinical trial - Fabbro, Michel; Lamy, Pierre-Jean; Touraine, Célia; Floquet, Anne; Ray-Coquard, Isabelle; Mollevi, Caroline (Frontiers in Oncology, 2024)
HE4 and CA-125 are used for Epithelial Ovarian Cancer (EOC) screening, diagnosis and follow-up. Our objective was to study HE4 and CA125 kinetics in patients treated for recurrent EOC. Serum samples were prospectively collected before the first chemotherapy cycle and every 3 months until disease progression. Data from 89/101 patients could be analyzed. At baseline, the median CA-125 and HE4 concentrations were 210 IU/L (7-10310) and 184 pM (31-4836). Among the 12 patients (13%) with normal CA-125 (<35 IU/L) concentration, 8 had HE4 concentration ≥75pM and among the 16 patients with normal HE4 concentration (18%), 12 had increased CA-125 concentration. The median nadir concentrations were 31 IU/L (3-8744) for CA-125 and 75 pM (20-4836) for HE4. The median times to nadir were 14 (0-130) weeks for CA-125 and 12 (0-52) weeks for HE4. In multivariate analysis, CA-125 and HE4 nadir concentrations (<35 IU/l, HR 0.35, 95% CI: 0.17-0.72; and <75 pM, HR 0.40, 95% CI: 0.20-0.79), time to CA-125 and HE4 nadir (>14 weeks; HR 0.37, 95% CI: 0.20-0.70; and >12 weeks, HR 0.43; 95% CI: 0.23-0.83) were prognostic factors of progression-free survival. More investigations on HE4 kinetics could help to better monitor patients with CA-125 concentration within normal values.